Kualitas Layanan dan Persepsi Manfaat terhadap Kepuasan Nasabah Menggunakan QRIS pada PT Bank Sumsel Bangka Belitung - Nur Annisa Fadli; Purwati Purwati; Markoni Badri (Politeknik Negeri Sriwijaya, 2024)
QRIS is a payment using the QR Code method that is easier, faster, and secure. Therefore the quality of service must be improved. This study aims to determine the use, service quality and perceived benefits of customer satisfaction using QRIS at PT Bank Sumsel Babel. This study uses a quantitative method which sources data from the results of questionnaires and data processing techniques using SPSS Version 26. This data processing uses multiple linear regression analysis. The results of this study conclude that the use of QRIS has an effect, because people in the current era use technology a lot for their daily activities and it is also more effective. The perception of benefits has an influence because the QRIS from the BSB bank is guaranteed confidentiality and is also safer to use than using cash. PT Bank Sumsel Babel must carry out socialization frequently and interestingly so that customers who do not know that transacting using QRIS get more benefits and benefits, and improve the quality of service even better and add features to QRIS so that it is maximized. Â